Evaluation of harvesting time and husk effects on retention of nutritional properties of boiled fresh orange maize hybrids - Alamu, Emmanuel Oladeji; Maziya-Dixon, B.B.; Olaofe, O.; Menkir, A. (2016)
This study evaluated the effects of harvesting time and husk on the proximate composition of boiled orange maize hybrids. Eight fresh orange maize hybrids were boiled with and without intact husk at 100oC using atmospheric cooking method and evaluated for proximate components. The results of analysis of variance [ANOVA] revealed that maturity [harvesting time] and method had significant effects [p ≤ 0.001] on all proximate components. There was a general decrease in dry matter [DM], ash and total sugar contents across harvest maturity stages. Protein and fat increased at 20DAP and 27DAP and then decreased at 34DAP. The unprocessed maize had optimum sugar content at 20DAP and optimum protein and fat contents at 27DAP. The optimum sugar and protein contents were found at 20DAP and 34DAP respectively for boiled maize without husk, while optimum sugar and protein contents were found at 20DAP for boiled maize with husk. Boiled maize with husk had higher retention of protein, total sugars and starch at 20DAP than boiled maize without husk. Thus, the best harvesting time to consume boiled maize is at 20DAP for optimum protein and sugar contents and it must be boiled with husk.